Perencanaan Para Sport Center sebagai sarana pembelajaran luar ruang bagi anak berkebutuhan khusus di SLB Negeri 1 Badung, Bali - Destiana, Audry Haniyah; Yusiana, Lury Sevita; Fitriana, Devvy Alvionita (Jurnal Arsitektur Lansekap, 2026)
Children with Special Needs (CSN) possess unique characteristics that require specialized learning approaches and supportive environments, including outdoor facilities that foster motor, social, and individual development. Special Needs School 1 Badung, as an educational institution for ABK, has yet to provide an optimal outdoor space. The urgency of planning such a space is driven by the need for facilities that channel students' talents and interests through appropriate physical activities. This study aims to design a Para Sport center as an inclusive and adaptive educational outdoor space to support physical and motor activities and the development of student talents. A descriptive qualitative method with a landscape planning approach was employed, comprising stages of identification, inventory, analysis, synthesis, and the formulation of planning concepts. The results indicate that the Para Sport center design must prioritize accessibility, safety, comfort, and the provision of diverse adaptive sports facilities tailored to the interests and abilities of ABK, such as boccia and athletics. This study concludes that inclusive outdoor spaces play a critical role in enhancing educational quality, channeling student potential, and improving physical and motor skills.